Sensitivity study to select the wet deposition scheme in an operational atmospheric transport model. (October 2021) - Quérel, Arnaud; Quélo, Denis; Roustan, Yelva; Mathieu, Anne
Abstract: The ability of operational atmospheric transport models to simulate the soil contamination caused by deposition processes is important in the response to a nuclear crisis. The Fukushima accident was characterized by wet deposition of Cs-137, which is difficult to simulate accurately based on observations. A sensitivity study investigated seven wet deposition schemes integrated into operational atmospheric transport models. Deposition maps produced from the multiple simulations are compared with each other and with the observed deposition. Similarities and discrepancies in average behavior are presented for a number of modeling cases on the basis of criteria representing soil contamination crisis management needs. This study confirms the importance of the wet deposition scheme in a crisis management context. None of the schemes used in the study are the best option to satisfy all the comparison criteria. This study suggests that crisis managers must not exclusively trust a single model for selecting responses. At the current time, it is preferable to use several wet deposition schemes in the modelling tools for emergency responses. Highlights: Select a wet deposition scheme in operational atmospheric transport models. Sensitivity study based on seven deposition schemes while varying the main inputs. Underline situations highly sensitive to the wet deposition scheme. Uncertainties in real case prevent an objective choice of the wet deposition scheme. Should use several wet deposition schemes for emergency response.